Attributes of physical education 4 students playing esports: A mixed study - Yagong, Kenneth (Edu Sportivo: Indonesian Journal of Physical Education, 2023)
Esports integration into PE 4 courses amidst COVID-19 is quite challenging for physical education instructors as part of the distance learning component. This study aimed to identify the attributes developed among the 70 PE 4 students playing Mobile Legends Bang Bang (MLBB) at Christ the King College de Maranding, Inc. The study utilised a triangulation mixed-methods design and revealed that most of the PE 4 male and female students (85.7%) spent at most 3 hours per day playing MLBB. Their top 2 rankings in MLBB were either epic or legendary, and their medal system scores reached either gold or gold MVP. The students' levels of attributes such as interpersonal communication, cooperation, integrity, self-discipline, teamwork, leadership, and problem-solving skills were developed. There was a significant relationship between the students' attributes and their MLBB medal system scores. Moreover, it revealed four themes that represented the experiences of the participants: (1) creating problems and difficulties that students have to overcome; (2) developing in the students the attributes for personal growth and interpersonal development; (3) allowing students to form meaningful relationships and interactions; and (4) giving students a sense of achievement and satisfaction. Hence, playing esports has enhanced the PE 4 students’ meaningful learning experiences and inspired them to embrace esports as part of the curriculum. For further validation, the same research is needed to identify the other areas or factors that affect playing eSports in physical education courses.